2019
DOI: 10.1186/s12964-019-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of MORC2 through its C-terminal coiled-coil domain enhances chromatin dynamics and promotes DNA repair

Abstract: Decondesation of the highly compacted chromatin architecture is essential for efficient DNA repair, but how this is achieved remains largely unknown. Here, we report that microrchidia family CW-type zinc finger protein 2 (MORC2), a newly identified ATPase-dependent chromatin remodeling enzyme, is required for nucleosome destabilization after DNA damage through loosening the histone-DNA interaction. Depletion of MORC2 attenuates phosphorylated histone H2AX (γH2AX) focal formation, compromises the recruitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…LDH activity was expressed as 'n moles of NADH formedÁmin À1 Álg À1 of protein'. *P < 0.05, **P < 0.01, and ***P < 0.001. structure either by protein-DNA or protein-protein interaction [15,[21][22][23]29]. Here, we have found that MORC2 coregulates LDHA expression by interacting with c-Myc (Figs S10 and S11).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…LDH activity was expressed as 'n moles of NADH formedÁmin À1 Álg À1 of protein'. *P < 0.05, **P < 0.01, and ***P < 0.001. structure either by protein-DNA or protein-protein interaction [15,[21][22][23]29]. Here, we have found that MORC2 coregulates LDHA expression by interacting with c-Myc (Figs S10 and S11).…”
Section: Discussionmentioning
confidence: 66%
“…MORC2 is not a transcription factor, but it can regulate the gene transcription by altering the chromatin structure either by protein–DNA or protein–protein interaction [15,21–23,29]. Here, we have found that MORC2 coregulates LDHA expression by interacting with c‐Myc (Figs S10 and S11).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…MORC2 is a member of the MORC ATPase superfamily, and it plays vital roles in diverse biological processes, such as lipogenesis, DNA damage repair, and chromatin remodeling. 31–33 MORC2 had been uncovered as an oncogene in liver cancer. 34 Moreover, miR-186-5p targeted MORC2 to curb metastasis and growth of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…MORC2 is a 1032-amino acid (AA) protein predicted to contain several functional domains. The Nterminal catalytically active ATPase module is composed of Gyrase B, Hsp90, histidine kinase, and MutL (GHKL) and S5-fold domains (AA residues 1-469), which has been mechanistically linked to gene transcription and DNA repair by remodeling chromatin [3][4].The CW-type zinc nger domain(AA residues 490-544) participates in chromatin regulation through the recognition of epigenetic signals [4].The C-terminal chromo-like domain(AA residues 795-850) is commonly found in eukaryotic chromatin proteins and can recognize methylated peptides in histones and nonhistone proteins [25].The coiled-coil domains is suggested to be an important structural determinant for protein assembly and molecular recognition [25]. It is interesting to note that the different mutations causing distinct changes in biochemical properties (Table 3) [6], which may be helpful to understand MORC2 mutations cause the complex range of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%